2015
DOI: 10.1186/s12871-016-0199-9
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular intracranial pressure monitoring improves the outcome of older adults with severe traumatic brain injury: an observational, prospective study

Abstract: BackgroundIntracranial pressure (ICP) monitoring is widely used in the management of patients with severe traumatic brain injury (TBI). However, there is limited evidence about the efficacy of ICP monitoring in older subjects (aged ≥65 years). This study evaluated the effect of intraventricular ICP monitoring on the outcome of older adults suffering from a severe TBI.MethodsThis prospective, observational study included 166 older TBI patients (aged ≥65 years) with Glasgow Coma scale (GCS) scores lower than 9 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 32 publications
0
32
0
1
Order By: Relevance
“…Our results are compatible with findings in other observational studies, indicating that ICP monitoring is benefi- cial for patients with severe TBI fulfilling the BTF criteria for ICP monitoring. 1,8,14,17,30,31 Moreover, in a recent metaanalysis of both observational and randomized controlled trials, the use of ICP monitors was found to be beneficial. 24 The heterogeneity in the effect of ICP monitors on outcome in the observational studies is perplexing.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are compatible with findings in other observational studies, indicating that ICP monitoring is benefi- cial for patients with severe TBI fulfilling the BTF criteria for ICP monitoring. 1,8,14,17,30,31 Moreover, in a recent metaanalysis of both observational and randomized controlled trials, the use of ICP monitors was found to be beneficial. 24 The heterogeneity in the effect of ICP monitors on outcome in the observational studies is perplexing.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies focusing on specific age demographics again had mixed results, however. These include an observational study showing improved hospital and 6-month mortality with ICP monitor placement in the elderly,7 as compared with a 2007–2008 NTDB study that did not find a survival benefit in patients over 55 years 5…”
Section: Discussionmentioning
confidence: 99%
“…This elevated mortality rate has been attributed to the higher risk of falls in this age group. Despite the high risk of mortality in elderly patients with severe TBI, the evidence for ICP monitor efficacy in this subgroup is limited 7. There is a void in the literature on the effect of ICP monitoring specifically in the elderly, as well as whether or not deferring ICP monitor placement in these patients is appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…9,10,14 The outcome of ICP monitoring in elderly is controversial, with some studies in favour andothers showing no major benefit. 32,33 Anticoagulant agents such as warfarin are associated with increased mortality, but such is not observed with antiplatelet agents especially when surgical imtervemtion is required. 34,35 The risk of post-traumatic epilepsy is higher in elderly and also the risk of delayed seizures is greater than early seizures when compared to younger adults.…”
Section: Discussionmentioning
confidence: 99%